2017
DOI: 10.4236/msa.2017.82009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Co-Cr-Mo Fluorapatite Nano-Composite Coatings by Pulsed Laser Deposition for Dental Applications

Abstract: Aim: The study was to fabricate FA nanopowder/Co-Cr-Mo dental alloy nanocomposite using pulsed laser deposition (PLD), and to evaluate bioactivity properties on simulated body fluid. Methods: In this work, the FA nanopowder was prepared by mixing calcium hydroxide (Ca(OH) 2 ), phosphorouspent oxide (P 2 O 5 ) and calcium fluoride (CaF 2 ) in a planetary high energy ball mill using zirconium vial. Fluorapatite (FA) nanopowder was processed in the form of pellet for pulsed laser deposition process. The Co-Cr-Mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Therefore, CaP was precipitated heterogeneously at the laser-irradiated substrate surface without the sedimentation of homogeneously precipitated CaP particles. The use of a liquid CaP source (CP solution) makes the LAB process different from other laser-assisted CaP coating techniques, such as pulsed laser deposition [9] and laser-assisted powder fusion [10], both of which use solid CaP sources. A comparison with a non-irradiated surface of the LAB-processed (30 min) substrate revealed that the CaP coating was confined to the laser-irradiated surface; the non-irradiated surface was not affected, even in the same substrate (Figure 2c), which indicates the essential role of laser irradiation to induce CaP precipitation on the Co−Cr alloy substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CaP was precipitated heterogeneously at the laser-irradiated substrate surface without the sedimentation of homogeneously precipitated CaP particles. The use of a liquid CaP source (CP solution) makes the LAB process different from other laser-assisted CaP coating techniques, such as pulsed laser deposition [9] and laser-assisted powder fusion [10], both of which use solid CaP sources. A comparison with a non-irradiated surface of the LAB-processed (30 min) substrate revealed that the CaP coating was confined to the laser-irradiated surface; the non-irradiated surface was not affected, even in the same substrate (Figure 2c), which indicates the essential role of laser irradiation to induce CaP precipitation on the Co−Cr alloy substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, Co−Cr alloys are categorized as bioinert materials; their osteoconductivity is insufficient compared to osteoconductive CaP compounds [4]. To remedy this shortcoming, various CaP coating techniques, such as plasma spraying [5], hot isostatic pressing [6], pressing/heating process [7], electrophoresis [8], pulsed laser deposition [9], laser-assisted powder fusion [10] and biomimetic process (supersaturated solution process) [11], have been applied to Co−Cr alloys.…”
Section: Introductionmentioning
confidence: 99%